Efeito do sistema de plantio e da frequência de irrigação sobre a cultura da batata (Solanum tuberosum L.) - C Segóvia, Feliciano; F da Silva, José; Bernardo, Salassier; R Condé, Alcides (Revista Ceres, 2025)
Four irrigation intervals were used with two planting methods for potatoes. This study was conducted at the Federal University of Vigosa under field conditions. Half of the potatoes were planted in a ten cm deep furrow and the other half at the soil surface. Both were covered with an additional ten cm of soil Four frequencies of irrigation (4, 8, 12 and 16 day intervals) were applied. Also, each type of planting had one check plot without irrigation. Before each irrigation, soil moisture was determined.